Improving the fretting biocorrosion of Ti6Al4V alloy bone screw by decorating structure optimised TiO2 nanotubes layer. (15th July 2020) - Luo, Jiajun; Tamaddon, Maryam; Yan, Changyou; Ma, Shuanhong; Wang, Xiaolong; Zhou, Feng; Liu, Chaozong
Abstract: TiO2 nanotubes (NT) has been demonstrated its potential in orthopaedic applications due to its enhanced surface wettability and bio-osteointegration. However, the fretting biocorrosion is the main concern that limited its successfully application in orthopaedic application. In this study, a structure optimised thin TiO2 nanotube (SONT) layer was successfully created on Ti6 Al4 V bone screw, and its fretting corrosion performance was investigated and compared to the pristine Ti6 Al4 V bone screws and NT decorated screw in a bone-screw fretting simulation rig. The results have shown that the debonding TiO2 nanotube from the bone screw reduced significantly, as a result of structure optimisation. The SONT layer also exhibited enhanced bio-corrosion resistance compared pristine bone screw and conventionally NT modified bone screw. It is postulated that interfacial layer between TiO2 nanotube and Ti6 Al4 V substrate, generated during structure optimisation process, enhanced bonding of TiO2 nanotube layer to the Ti6 Al4 V bone screws that leading to the improvement in fretting corrosion resistance. The results highlighted the potential SONT in orthopaedic application as bone fracture fixation devices.